Osteology and Postmetamorphic Development of Telmatobius oxycephalus (Anura: Telmatobiidae) With an Analysis of Skeletal Variation in the Genus - Barrionuevo, Jose Sebastian (2012)
The osteological diversity among species of Telmatobius has been considered conservative. Nonetheless, the degree of ossification of several features varies both intraspecifically and interspecifically. Herein, intraspecific osteological variation and post metamorphic ontogenetic changes in osteological features are described in Telmatobius oxycephalus. These data are compared with published descriptions of congeners. There is a considerable intraspecific osteological variation in T. oxycephalus, with cranial characters varying polymorphically, and the hyoid and postcranial characters being sexually dimorphic. This intraspecific variation is expressed by subtle differences in the degree of ossification or mineralization. Interspecific variation also can be described in terms of differential development of osteological features; these differences are more obvious than intraspecifically variable characters. The adult skeletons of several species of Telmatobius resemble the morphology observed in early stages of postmetamorphic development of T. oxycephalus. This is especially evident in the neopalatines, parasphenoid, sphenethmoid, exoccipitals, prootics, vomers, nasals, and plectra. These results suggest that within the conservative osteological architecture of Telmatobius, the variation observed is the result of heterochronic changes during the ossification process.